The effect of a paraffin screen on the neutron dose at the maze door of a 15 MV linear accelerator. Issue 8 (3rd July 2013) - Krmar, M.; Nikolić, D.; Kuzmanović, A.; Kuzmanović, Z.; Ganezer, K.
Abstract : Purpose: : The purpose of this study was to explore the effects of a paraffin screen located at various positions in the maze on the neutron dose equivalent at the maze door. Methods: : The neutron dose equivalent was measured at the maze door of a room containing a 15 MV linear accelerator for x‐ray therapy. Measurements were performed for several positions of the paraffin screen covering only 27.5% of the cross‐sectional area of the maze. The neutron dose equivalent was also measured at all screen positions. Two simple models of the neutron source were considered in which the first assumed that the source was the cross‐sectional area at the inner entrance of the maze, radiating neutrons in an isotropic manner. In the second model the reduction in the neutron dose equivalent at the maze door due to the paraffin screen was considered to be a function of the mean values of the neutron fluence and energy at the screen. Results: : The results of this study indicate that the equivalent dose at the maze door was reduced by a factor of 3 through the use of a paraffin screen that was placed inside the maze. It was also determined that the contributions to the dosage from areas that were not covered by the paraffin screen as viewed from the dosimeter, were 2.5 times higher than the contributions from the covered areas. This study also concluded that the contributions of the maze walls, ceiling, and floor to the total neutron dose equivalent were an order of magnitude lower than those from the surface at the far end of the maze. Conclusions: : This study demonstrated that a paraffin screen could be used to reduce the neutron dose equivalent at the maze door by a factor of 3. This paper also found that the reduction of the neutron dose equivalent was a linear function of the area covered by the maze screen and that the decrease in the dose at the maze door could be modeled as an exponential function of the product ϕ ¯ · E ¯ at the screen.